Ankara Temple (Monumentum Ancyranum/Temple of Augustus and Rome) restoration. (June 2015) - Gökdemir, Ahmet; Demirel, Can; Yeğin, Yavuz; Şimşek, Zeynel
Abstract: Temple of Augustus and Rome, also referred as Monumentum Ancyranum (Ankara Temple), is located near Haci Bayram Mosque in Ulus, Ankara. The temple which was built on behalf of Phrygian God 'Men' in 2nd century BC has been destroyed. The temple whose remains are present, on the other hand, was built for Roman Emperor 'Augustus' (Gaius Octavius) in 25 BC in the name of a commitment sign by King Pilamenes, the son of King Amintos, of Galatia. The positions of the 4 columns in the doorways and 2 columns in the rear sides are recognizable. Currently, only the sidewalls and ornamented door part are remaining. The original testament of Augustus in Temple of Rome, which is written in Latin and Greek and is telling the achievements of Augustus, is imitated in the mosque that is neighboring the wall of Monumentum Ancyranum. Some parts of the patina are spilled because of the climatic parameters (wind, heat, precipitation, and frost). As a result of the petrographic analysis made on the spilled parts of patina, it is concluded that the temple, which has a great importance in the world history, has to be restorated. As a result of the analyses (scanning electron microscope (SEM) analysis, EDS, and X-ray diffraction (XRD) analysis), inner and outer sides of Naos are being constructed without mortar. In the parts, which are broken from the main body, calcium carbonate (CaCO3 ) and magnesium carbonate (MgCO3 ) are detected. Besides, it is observed that the main body of the temple is mainly consisting of calcium mineral. If this temple will be restored in the future, it is important to watch out for the calcium mineral property of the building.